Educational Institution Digital-Based Marketing Strategy; Through Social Media - MY, Mahmud; Fadlilah, Fadlilah; Salahuddin, Salahuddin; Chaniago, Fransisko; Fitriani, Suci; Sakunti, Sri Ramdayeni (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2024)
An educational institution must engage in marketing as it becomes mandatory. An educational institution's marketing function should be implemented with the intention of improving the institution's reputation and attracting new students. Social media plays a significant part in marketing as a networking platform. This is due to the potential communication function of social media. Therefore, an educational institution must implement a marketing strategy to keep and pique the attention of parents and the community by implementing a digital-based marketing strategy through social media. The goal of this study is to investigate and evaluate social media-based digital marketing methods for educational institutions at Madrasah Tsanawiyah Raudhatul Islamiyah. This study used a qualitative approach combined with a descriptive analysis technique. direct interviews with important parties, including teachers, school officials, and social media managers. The study's findings demonstrate that social media in the forms of Facebook, Instagram, and Youtube are utilized to promote educational institutions at Madrasah Tsanawiyah Raudhatul Islamiyah. Whereas Whatsapp is used to answer questions from guardians and prospective student guardians which is used as a medium to communicate directly in order to register prospective students via online.